OB-Rb gene transfer to leptin-resistant islets reverses diabetogenic phenotype - Wang, May-Yun (The National Academy of Sciences, 1998)
In obese Zucker diabetic fatty (ZDF) rats with mutant leptin receptors, pancreatic islets have an ≈50-fold increase in fat (TG), overproduce nitric oxide (NO), and lack a normal proinsulin mRNA response to fatty acids. We overexpressed the wild-type full-length “b” isoform of the leptin receptor (OB-Rb) in ZDF islets by perfusing ZDF pancreata with recombinant adenovirus containing the cDNA encoding OB-Rb. In cultured islets isolated from these animals, leptin lowered islet TG by 87% and completely blocked TG formation from free fatty acids. Overproduction of NO was reduced, and the preproinsulin mRNA response to free fatty acids was restored. This establishes defective leptin action as the proximate cause of lipotoxic diabetes in ZDF rats.